5-Aminolaevulinate hydro-lyase from yeast isolation and purification - Clara de Barreiro, O.L. (1967)
An enzyme, aminolaevulinate dehydratase (5-aminolaevulinate hydro-lyase (adding 5-aminolaevulinate and cyclizing), EC 4.2.1.24), which catalyzes the following reaction: A figure is presented has been isolated from yeast. Its purification and some of its properties have been studied. 5-Aminolaevulinate synthetase, another enzyme involved in porphyrin biosynthesis, has been detected in the mitochondrial particles. © 1967.